Challenges faced by undergraduate vocal students in preparation for their mid-term studio examinations / Viviannie Longinu - Longinu, Viviannie (2014)
This study aims to investigate the challenges faced by undergraduate vocal student in preparation for their mid-term studio examination. It identified student's practice preparation and to identify good practices and provide insights into how students manage their problems in preparing for their mid-term studio examinations. The important of this study is to learn more about the problems that often faced by vocal students in terms ofpreparation and a proper technique practice. Besides that, it is to investigate the more ways on how vocal students deal with this problems in term of mental and physical preparation to face the midterm studio examination.